2021
DOI: 10.3847/1538-4357/abce66
|View full text |Cite
|
Sign up to set email alerts
|

The Fundamental Plane of Massive Quiescent Galaxies at z ∼ 2

Abstract: We examine the Fundamental Plane (FP) and mass-to-light ratio (M/L) scaling relations using the largest sample of massive quiescent galaxies at 1.5<z<2.5 to date. The FP (r e ,σ e ,I e ) is established using 19 UVJ quiescent galaxies from COSMOS with Hubble Space Telescope H F160W rest-frame optical sizes and X-shooter absorption line-measured stellar velocity dispersions. For a very massive,, subset of eight quiescent galaxies at z>2, from Stockmann et al., we show that they cannot passively evolve to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Over the last decade, incredibly dedicated effort and investment on ground-based 8-10 m telescopes and the Hubble Space Telescope (HST) have repeatedly pushed the spectroscopic confirmation of the existence of quiescent galaxies to z ∼ 4, when the universe was only 1.5 Gyr old, progressively challenging theoretical models of galaxy formation and evolution (Gobat et al 2012;Marsan et al 2015;Glazebrook et al 2017;Kado-Fong et al 2017;Forrest et al 2020a). Multiobject deep near-IR (NIR) (i.e., rest-frame optical) spectroscopy of 2 < z < 4 quiescent galaxies has allowed for the measurements of their stellar populations and star formation histories (Schreiber et al 2018;Belli et al 2019;D'Eugenio et al 2020D'Eugenio et al , 2021Estrada-Carpenter et al 2020;Forrest et al 2020aForrest et al , 2020bSaracco et al 2020;Valentino et al 2020), kinematics, sizes, andmorphologies (van de Sande et al 2013;Belli et al 2017;Hill et al 2016;Newman et al 2018;Tanaka et al 2019;Estrada-Carpenter et al 2020;Saracco et al 2020;Esdaile et al 2021;Stockmann et al 2021;Forrest et al 2022), metallicity (Morishita et al 2019;Saracco et al 2020) , hereafter corresponding to around a third of the characteristic stellar mass of the galaxy stellar mass function; e.g., Muzzin et al 2013) quiescent galaxy at z > 2 has been spectroscopically confirmed yet, preventing the exploration of quenching mechanisms to the low-stellarmass regime at cosmic noon. For example, while some form of feedback generally attributed to active galactic nuclei (AGNs) is supposed for the quenching of galaxies at the massive end, it is unclear whether AGN feedback can also operate in low-mass galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, incredibly dedicated effort and investment on ground-based 8-10 m telescopes and the Hubble Space Telescope (HST) have repeatedly pushed the spectroscopic confirmation of the existence of quiescent galaxies to z ∼ 4, when the universe was only 1.5 Gyr old, progressively challenging theoretical models of galaxy formation and evolution (Gobat et al 2012;Marsan et al 2015;Glazebrook et al 2017;Kado-Fong et al 2017;Forrest et al 2020a). Multiobject deep near-IR (NIR) (i.e., rest-frame optical) spectroscopy of 2 < z < 4 quiescent galaxies has allowed for the measurements of their stellar populations and star formation histories (Schreiber et al 2018;Belli et al 2019;D'Eugenio et al 2020D'Eugenio et al , 2021Estrada-Carpenter et al 2020;Forrest et al 2020aForrest et al , 2020bSaracco et al 2020;Valentino et al 2020), kinematics, sizes, andmorphologies (van de Sande et al 2013;Belli et al 2017;Hill et al 2016;Newman et al 2018;Tanaka et al 2019;Estrada-Carpenter et al 2020;Saracco et al 2020;Esdaile et al 2021;Stockmann et al 2021;Forrest et al 2022), metallicity (Morishita et al 2019;Saracco et al 2020) , hereafter corresponding to around a third of the characteristic stellar mass of the galaxy stellar mass function; e.g., Muzzin et al 2013) quiescent galaxy at z > 2 has been spectroscopically confirmed yet, preventing the exploration of quenching mechanisms to the low-stellarmass regime at cosmic noon. For example, while some form of feedback generally attributed to active galactic nuclei (AGNs) is supposed for the quenching of galaxies at the massive end, it is unclear whether AGN feedback can also operate in low-mass galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of massive quiescent galaxies at z = 2-4 (Cimatti et al 2004(Cimatti et al , 2006van Dokkum et al 2004;Stockmann et al 2020;Valentino et al 2020), it has been hypothesised that their progenitors in the early Universe must be short-lived massive starbursts at z > 4 (Casey et al 2014;Toft et al 2014). Analysis of Atacama Large Millimeter Array (ALMA) observations of far-infrared ultra-red sources has identified galaxies at z = 3-7 (Iono et al 2016;Oteo et al 2016Oteo et al , 2017Gómez-Guijarro et al 2018;Marrone et al 2018) with extreme infrared luminosities (log L IR (L ) > 13) and star Calibrated ALMA, JWST, and HST images of SPT0311-58 system images are also available at the CDS via anonymous ftp to cdsarc.cds.unistra.fr (130.79.128.5) or via https:// cdsarc.cds.unistra.fr/viz-bin/cat/J/A+A/671/A105…”
Section: Introductionmentioning
confidence: 99%